Designing optimal routing solutions for logistic operations. - Ignatius, Joshua (Universiti Sains Malaysia, 2015)
One way to generate a higher recycling rate is to handle materials recovery efficiently. Conventional recycling schemes require the recylates to be "clean", i.e. separated prior to coming into the material recovery facility (MRF). However, it is inconvenient to pre-sort their recyclates. To solve this problem, we propose multiple bins to be assigned to each personnel to maximize conveyor belt usage.We model the unload-and-switch cycle through a 2-nested routing problem. A numerical example validates the approach.